Boosting OCR Accuracy Using Crowdsourcing - Wang, Shuo-Yang; Wang, Ming-Hung; Chen, Kuan-Ta (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
Book digitizing is an important work in preserving ancient heritages. However, digitizing books contains a series of labor-intensive works, and one of them is to verify optical character recognition (OCR) outcomes. In this paper, we propose a crowdsourceable OCR verification method. Using our method, content holders are able to leverage the power of crowds to complete verification tasks and avoid content leakage. From the experiment results, our method is more efficient and reliable than the traditional method.